2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27667
|View full text |Cite
|
Sign up to set email alerts
|

Board # 100 : Research Design, Data Collection, and Assessment Methods for an Integrated STEM Education Model (Work in Progress)

Abstract: design and cognition seeking to better understand how young students learn design and how design improves STEM education. He joined a team of researchers to create a program to improve learning STEM in elementary grades, and the team was awarded an NSF Math and Science partnership called Science Learning Through Engineering Design (SLED). Kelley is currently the PI on an NSF I-Test project called Teachers and Researchers Advancing Integrated Lessons in STEM (TRAILS). TRAILS prepares science and technology educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…In addition to this, Laksmiwati et al (2020) argued that in the implementation of STEM, the TDP becomes very significant in the development of students' thinking and problem-solving in STEM activities. In accordance with the above, many initiatives have been taken to analyse the implementation of STEM activities in classrooms, and the results of those studies showed that most of the activities were connected to the TDP (Knowles et al, 2017;McFadden & Roehrig, 2019).…”
Section: Literature Reviewmentioning
confidence: 86%
“…In addition to this, Laksmiwati et al (2020) argued that in the implementation of STEM, the TDP becomes very significant in the development of students' thinking and problem-solving in STEM activities. In accordance with the above, many initiatives have been taken to analyse the implementation of STEM activities in classrooms, and the results of those studies showed that most of the activities were connected to the TDP (Knowles et al, 2017;McFadden & Roehrig, 2019).…”
Section: Literature Reviewmentioning
confidence: 86%